Increased Antibody Response to Fucosylated Oligosaccharides and Fucose-Carrying Bacteroides Species in Crohn’s Disease - Kappler, Katharina; Lasanajak, Yi; Smith, David F.; Opitz, Lennart; Hennet, Thierry (Frontiers in Microbiology, 2020)
Inflammatory bowel disease is associated with intestinal dysbiosis and with elevated antibody production towards microbial epitopes. The underlying processes linking the gut microbiota with inflammation are still unclear. Considering the constant induction of antibodies by gut microbial glycans, the aim of this study was to address whether the repertoire of carbohydrate-specific antibodies is altered in Crohn’s disease or ulcerative colitis. IgG and IgM reactivities to mucosal glycans were tested in blood serum from 20 healthy control subjects, 17 ulcerative colitis patients, and 23 Crohn’s disease patients using glycan arrays. An increased IgG and IgM reactivity towards fucosylated oligosaccharides was detected in Crohn’s disease but not in ulcerative colitis. To address the antibody reactivity to the gut microbiota, IgG binding to members of a complex intestinal microbiota was measured and observed to be increased in sera of patients with Crohn’s disease. Based on the elevated reactivity to fucosylated oligosaccharides, gut bacteria were tested for recognition by the fucose-binding Aleuria aurantia lectin. Bacteroides stercoris was detected in IgG- and lectin-positive fractions and reactivity of Aleuria aurantia lectin was demonstrated for additional Bacteroides species. IgG reactivity to these Bacteroides species was significantly increased in inflammatory bowel disease patients, indicating that the increased reactivity to fucosylated oligosaccharides detected in Crohn’s disease may be induced by fucose-carrying intestinal bacteria. Enhanced antibody response to fucosylated epitopes may have systemic effects by altering the binding of circulating antibodies to endogenous glycoproteins.